Electro-Optic Photonic Integrated Circuits for Radio Frequency Multiplication and Translation - Hasan, Gazi Mahamud (Université d'Ottawa / University of Ottawa, 2020)
The ever-growing data traffic and super broadband services demanded by the end users have led the wireless communication network to undergo rapid development in terms of capacity, bandwidth, cost and mobility. The low-power, mature lower frequency bands are already congested and offer small capacity in wireless communication. On the other hand, the high capacity high frequency wireless system is inherently power hungry, costly and imposes complicated coverage schemes. This bottleneck has introduced the radio-over-fiber (RoF) system as a viable solution for broadband wireless access networks. The aim of this thesis is to address two major aspects of a broadband wireless access network using a distributed antenna system complemented by a digital coherent optical RoF link: the millimeter-wave (mm-wave) carrier generation at downlink and efficient single sideband (SSB) modulation at uplink and their configuration in electro-optic photonic integrated circuit format. An optical path tracing method is proposed to transform any photonic circuit consisting of linear and time invariant optical components to its parallel counterpart comprising a collection of optical paths, each characterized by the transmission response of the element within it. This method is exploited to address the functionality of a photonic frequency multiplication circuit with a multiplication factor of eight where the time variance is handled by a focus on pure RF carriers and the Jacobi-Anger expansion. The series architecture consisting of four Mach-Zehnder modulator enables its application in a low RF drive condition with similar performance when compared to different functionally equivalent architectures. The concept of a frequency multiplication circuit as a stable, tunable means of millimeter-wave generation can be extended to incorporate polarization modulators instead of conventional Mach-Zehnder modulators due to the fact that the cascade of polarization modulator and polarizer provides an intensity modulator whose biasing condition can be set by the polarizer angle and polarization state of the input light to each polarization modulator. The employment of polarization modulator can avoid DC bias drift and feasible discrete component implementation can be achieved which is important in a research environment to establish the proof of concept. One of the circuits can access the millimeter-wave band for a wide range of modulation index; the other circuit can offer a RF power advantage in a moderate range of modulation index. Both circuits can provide a multiplication factor of eight which enables a low RF frequency source requirement. Simulation using industry standard software tools are used to validate theoretical predictions of the abovementioned circuits and their robustness against non-ideal factors are analyzed. In addition, the frequency translation property of a single sideband modulator based on a generalized Mach-Zehnder interferometer structure consisting of four Mach-Zehnder modulator in parallel is experimentally demonstrated. The multi-functional photonic circuit fabricated on silicon on insulator platform can provide sub-carrier generation, in-phase and quadrature (IQ) modulation and frequency multiplication functionalities in addition to the frequency conversion. The selection of the function is determined by the biasing condition of the modulators and RF drive specification which can be controlled externally. The employment of the multimode interference splitter/combiner can offer DC bias less operation due to its intrinsic phase relationship among the ports providing the necessary optical phase shift. Spatial separation of the up- and down-converted optical output opens the door for remote heterodyning operation. A carrier suppression of >20 dB and spurious sideband suppression > 12 dB relative to the principle harmonics is achieved when the circuit is operated as a frequency shifter with bias voltage tuning only. The generalized Mach-Zehnder interferometer structure can be extended to support in-phase and quadrature modulation for any number of constituent phase modulators, which provide a general theory of in-phase and quadrature modulation. From this theory, the lowest dimension of the interferometer structure is found to be three which implies that a three phase modulator structure, in contrast to the orthodox four phase modulator structure, can provide in-phase and quadrature modulation when the drive signals to the phase modulators are linear combinations of in phase and quadrature component of the signal. A system simulation is used to validate its operation as an in phase and quadrature and single sideband modulator.
Keywords: Radio-over-Fiber technology; Millimeter-wave generation; Frequency translation; Electro-optic Photonic integrated circuit; Mach-Zehnder modulator; Polarization modulator; IQ modulation; SSB modulation; Silicon-on-Insulator